(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
When a people think about language, they try to find answers to the questions of what language is, how it came about, whether it is a part of man or not, and whether society has an impact on a language. Many linguists have done a lot of research on these questions and mentioned some facts. This article describes how language can be given a true definition, and discusses about what kind of phenomenon language is, social or natural one.